Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

The Lerch transcendent is given by $$ \Phi(z, s, \alpha) = \sum_{n=0}^\infty \frac { z^n} {(n+\alpha)^s}. $$

While computing $\sum_{m=1}^{\infty} \sum_{n=1}^{\infty} \sum_{p=1}^{\infty}\frac{(-1)^{m+n+p}}{m+n+p}$, the expression $$ -\sum_{k=1}^{\infty} \Phi(-1, 1, 1+k) $$ came up. Is there an (easy?) way to calculate that?

Writing it down, it gives: $$ -\sum_{k=1}^{\infty} \Phi(-1, 1, 1+k)= \sum_{k=1}^{\infty} \sum_{n=1}^\infty \frac { (-1)^n} {n^{k+1}} $$ Is changing the summation order valid?

There is a relation to the Dirichlet $\eta$ function $$ \eta(s) = \sum_{n=1}^{\infty}{(-1)^{n-1} \over n^s} = \frac{1}{1^s} - \frac{1}{2^s} + \frac{1}{3^s} - \frac{1}{4^s} + \cdots $$ but (how) can I use that? The double series then reads $$ \sum_{k=1}^{\infty} \sum_{n=1}^\infty \frac { (-1)^n} {n^{k+1}}= -\sum_{k=1}^{\infty} \eta(k+1). $$ Interestingly, that among the values for $\eta$, given at the WP, you'll find $\eta(0)=1/2$ related to Grandi's series and $\eta(1)=\ln(2)$, both show up in my attempt to prove the convergence of the triple product given there.

share|improve this question
    
If the series converges absolutely, then you can change the order of summation –  Mhenni Benghorbal Jul 25 '12 at 12:18
    
@MhenniBenghorbal $\sum_{n=1}^\infty \frac { 1} {n^{k+1}}=\zeta(k+1)$, so it converges absolutely for $k\ge 1$, right? –  draks ... Jul 25 '12 at 12:45
    
draks:The double series has to converge absolutely. –  Mhenni Benghorbal Jul 25 '12 at 12:53
    
@MhenniBenghorbal and the double doesn't: $\lim_{n\to \infty}\sum_2^n \zeta(n)=\infty $. Thanks –  draks ... Jul 25 '12 at 13:02
    
@draks:any time. –  Mhenni Benghorbal Jul 25 '12 at 13:06

1 Answer 1

up vote 3 down vote accepted

The double series $\displaystyle\sum_{k=1}^{\infty} \sum_{n=1}^\infty \frac { (-1)^n} {n^{k+1}}$ diverges.

To see this, one can imitate the strategy used in the answer to the other question, and use the identity $$ \frac1{n^{k+1}}=\int_0^{+\infty}\mathrm e^{-ns}\frac{s^k}{k!}\,\mathrm ds. $$ Thus, for every $k\geqslant1$, $$ \sum_{n=1}^\infty \frac { (-1)^n} {n^{k+1}}=\int_0^{+\infty}\sum_{n=1}^\infty(-1)^n\mathrm e^{-ns}\frac{s^k}{k!}\,\mathrm ds=\int_0^{+\infty}\frac{-\mathrm e^{-s}}{1+\mathrm e^{-s}}\frac{s^k}{k!}\,\mathrm ds. $$ Since $1+\mathrm e^{-s}\leqslant2$ uniformly on $s\geqslant0$, $$ \sum_{n=1}^\infty \frac { (-1)^n} {n^{k+1}}\leqslant-\frac12\int_0^{+\infty}\mathrm e^{-s}\frac{s^k}{k!}\,\mathrm ds=-\frac12. $$ This proves that the double series diverges.

Edit: More directly, each series $\displaystyle\sum_{n=1}^\infty \frac { (-1)^n} {n^{k+1}}$ is alternating hence it converges and the value of its sum is between any two successive partial sums.

For example, $\displaystyle\sum_{n=1}^\infty \frac { (-1)^n} {n^{k+1}}\leqslant\sum_{n=1}^2 \frac { (-1)^n} {n^{k+1}}=-1+\frac1{2^{k+1}}\leqslant-\frac34$ for every $k\geqslant1$. QED.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.